2010
DOI: 10.1111/j.1502-3885.2010.00180.x
|View full text |Cite
|
Sign up to set email alerts
|

The Littorina transgression in the southwestern Baltic Sea: new insights based on proxy methods and radiocarbon dating of sediment cores

Abstract: Rößler, D., Moros, M. & Lemke, W. 2010: The Littorina transgression in the southwestern Baltic Sea: new insights based on proxy methods and radiocarbon dating of sediment cores. Boreas, 10.1111/j.1502‐3885.2010.00180.x. ISSN 0300‐9483. The Littorina transgression is one of the most pronounced environmental events in the Holocene history of the Baltic Sea. It changed the hydrographic system from the freshwater Ancylus Lake into the brackish‐marine Littorina Sea. Here, 18 cores from two western Baltic basins, Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 39 publications
3
52
0
Order By: Relevance
“…A continuous basal sediment sequence in C3 suggests the autochthonous formation of the sediments, showing sand deposited under freshwater conditions, followed by gyttja deposited during wetland conditions and peat accumulation during the Littorina transgression. Basal peat deposits are frequently used to constrain past sea levels (Lampe and Janke, 2004;Rößler et al, 2011;Heinrich et al, 2017). In principle, the available 14 C ages agree with and support the local Fischland and North Rügen Holocene sea level rise curves (Figure 6) established by Lampe et al (2010), but with a slight tendency toward lower sea level as determined by samples B6.1 and B6.2.…”
Section: Formation Time and Local Sea Level Risementioning
confidence: 82%
“…A continuous basal sediment sequence in C3 suggests the autochthonous formation of the sediments, showing sand deposited under freshwater conditions, followed by gyttja deposited during wetland conditions and peat accumulation during the Littorina transgression. Basal peat deposits are frequently used to constrain past sea levels (Lampe and Janke, 2004;Rößler et al, 2011;Heinrich et al, 2017). In principle, the available 14 C ages agree with and support the local Fischland and North Rügen Holocene sea level rise curves (Figure 6) established by Lampe et al (2010), but with a slight tendency toward lower sea level as determined by samples B6.1 and B6.2.…”
Section: Formation Time and Local Sea Level Risementioning
confidence: 82%
“…The youngest date of 7200 cal BP was found in the Arkona Basin (Moros et al 2002, Rößler et al 2011. The problem of age discrepancy was described by Kortekaas et al (2007) and Rößler et al (2011) where bulk 14 C ages, 14 C ages of macrofossils and OSL ages of marine sediment were compared. The authors concluded that the bulk 14 C ages are ~1000 years too old, because of possible sediment mixing with older carbon and indicated that the calcareous fossils are more suitable for dating.…”
Section: Littorina Sea Stagementioning
confidence: 99%
“…The onset of marine environment in the Gdańsk Basin was dated at around 7600 cal BP (Emelyanov and Vaikutienė 2013). The youngest date of 7200 cal BP was found in the Arkona Basin (Moros et al 2002, Rößler et al 2011. The problem of age discrepancy was described by Kortekaas et al (2007) and Rößler et al (2011) where bulk 14 C ages, 14 C ages of macrofossils and OSL ages of marine sediment were compared.…”
Section: Littorina Sea Stagementioning
confidence: 99%
See 2 more Smart Citations